ANALISIS PENYELENGGARAAN POS UPAYA KESEHATAN KERJA (POS UKK) DI UPTD PUSKESMAS KOTO BARU TAHUN 2025 - Vidia Putri Maharani (LPPM Universitas Awal Bros, 2026)
The Occupational Health Effort Post (Pos Upaya Kesehatan Kerja/Pos UKK) is a community-based health service designed to improve the occupational health and safety of informal sector workers through promotive, preventive, basic curative, and rehabilitative interventions. However, the implementation of Pos UKK in many community health centers remains suboptimal due to various organizational and resource-related constraints. This study aimed to analyze the implementation of the Occupational Health Effort Post (Pos UKK) at the Koto Baru Community Health Center in 2025 and to identify factors influencing its implementation as the basis for developing improvement strategies. This study employed a descriptive qualitative approach using a case study design. Data were collected through in-depth interviews with key informants, field observations, and document reviews. Data were analyzed using thematic analysis, while source and method triangulation were applied to ensure data credibility. The findings revealed that the implementation of Pos UKK had not been carried out optimally due to the absence of a dedicated budget, limited management commitment, inadequate competency of health personnel and occupational health cadres, weak cross-sectoral coordination, and the lack of a structured monitoring and evaluation system. Recommended improvement strategies include strengthening human resource capacity through training, policy advocacy to secure financial support, enhancing cross-sector collaboration, and establishing a sustainable monitoring and evaluation system. These strategies are expected to improve the effectiveness of Pos UKK implementation and strengthen occupational health services for informal sector workers.